Le pouvoir discrétionnaire de l'administration exercé sous forme de normes administratives : les directives - Filion, Michel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
This paper attempts to describe and assess the legal position in respect of guidelines, directives, manuals and similar instruments issued by administrative authorities. It first reviews the statutory or other legal basis for the power to issue such instruments. Particular attention is paid to the recognition by the courts of an implicit authority to formulate instructions to subordinate officials, as part of general managing and supervisory powers. The author then outlines the specific features of directives, as compared with regulations. Both classes of instruments usually contain rules of fairly general application. Both can be seen as useful means of structuring the exercice of discretionary decision-making powers. Directives, guidelines, manuals and the like, however, set a particular emphasis on the provision of guidance or even imperative instructions for officials in the discharge of their duties, while regulations apply just as statutes do, to the general public as well as to civil servants. Great weight —perhaps an excessive weight — was attached to this distinction in the reasons of Pigeon J. in the first Martineau case, which is discussed at some length. The question of unpublished directives becoming in fact a body of « secret law » is then surveyed. The limited scope of the federal Statutory Instruments Act in this respect is underlined, and the author argues for selective adoption of public rule-making procedures, requirements for publication in official gazettes, and referral to parliamentary committees. Finally, the paper surveys the present state of the law as regards judicial review of directives. While review may bear on the vires for the making of the directive, much as in the case of regulations, it more often occurs when a discretionary decision is challenged before the courts on the grounds that the decision-maker fettered its own discretion by inflexibly applying self-made guidelines where individual determination was called for, or by submitting to directives from some other authority. In cases where judicial intervention is not possible, recourse may be had to ombudsmen ; the experience of the Public Protector in Quebec in connection with directives and guidelines is described.